TRANSMISI HARGA TEH HITAM GRADE DUST INDONESIA - Adinugroho, Muhammad Fadhil; Harmini, Harmini (Forum Agribisnis, 2011)
The objectives of this paper are (1) to analyze the relationship of âdust gradeâ tea price at Jakarta, Colombo and Guwahati Tea Auction Markets, and (2) to perform Vector Autoregression (VAR) models in order to forecast the âdust gradeâ tea price at Jakarta Tea Auction Market. Grade dust tea is used to make the tea bag. The average weekly price of dust grade tea from the third week of February 2009 until the second week of April 2011 was used in this analysis. The results showed that firstly, there was no significant price transmission from Colombo and Guwahati Tea Auction Markets to Jakarta Tea Auction Market. There was no significant co-integration among the three markets. As a matter of fact, the price of dust grade tea at Jakarta Tea Auction Market was affected by its price of one week earlier at its own market. Secondly, NaÃ¯ve model was more accurate compared to VAR model in order to forecast the price of dust grade tea at Jakarta Tea Auction Market. Further research is needed in order to perform the more accurate forecasting model to predict the price of dust grade tea at Jakarta Tea Auction Market.